1993
DOI: 10.1111/j.1365-2672.1993.tb05198.x
|View full text |Cite
|
Sign up to set email alerts
|

A note on lactobacilli and β‐glucuronidase activity in the intestinal contents of mice

Abstract: A comparison was made of caecal beta-glucuronidase activity in the caecal contents of mice with or without lactobacilli as members of the normal microflora. Male mice that did not have lactobacilli as intestinal inhabitants had approximately 52% more caecal beta-glucuronidase activity than their female counterparts. Colonization of male mice by lactobacilli reduced the beta-glucuronidase activity to that of female mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Previous studies have observed ␤-glucuronidase activity in some gram-positive inhabitants of the GI tract, including three species of lactobacilli, but in no case have the genes responsible for these activities been identified. Of the three Lactobacillus species previously studied, L. delbrueckii, L. fermentum, and L. rhamnosus, only the enzyme activity from L. rhamnosus has been partially characterized (37,42). Thus, this report describes the first gusA gene to be cloned from a bacterial source other than E. coli.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have observed ␤-glucuronidase activity in some gram-positive inhabitants of the GI tract, including three species of lactobacilli, but in no case have the genes responsible for these activities been identified. Of the three Lactobacillus species previously studied, L. delbrueckii, L. fermentum, and L. rhamnosus, only the enzyme activity from L. rhamnosus has been partially characterized (37,42). Thus, this report describes the first gusA gene to be cloned from a bacterial source other than E. coli.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, their frequent exposure to bile is reflected in the common occurrence of conjugated bile acid hydrolysis among different species (12,19). Lactobacilli themselves have not traditionally been associated with ␤-glucuronidase activity, however, and there have been, to date, only two reports of ␤-glucuronidase-like activity in lactobacilli (37,42). It has been unclear, however, whether this ␤-glucuronidase activity was the result of a true ␤-glucuronidase enzyme or reflected the activity of some other enzyme.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Weighed fecal samples were diluted approximately 1:10 in 0.1 M sodium phosphate broth (pH 6.5) and used to measure ␤-glucuronidase activity (15). Similarly, a fecal homogenate in 0.01 M potassium phosphate buffer (pH 7.0) was used to measure the azoreductase activity of each sample (14).…”
Section: Methodsmentioning
confidence: 99%
“…Although physiological conditions in vivo are vastly different from in vitro model systems used for most studies, the presence of lactic acid bacteria in the intestine is postulated to limit the growth, metabolism or survival of other enteric bacteria, which may in turn limit pathogenic or toxigenic effects (7)(8)(9). Many other biological effects have been attributed to lactic acid bacteria, such as bile salt deconjugation (10), induction of higher tolerance to lactose when given to lactoseintolerant subjects (11,12), anticholesterolemic effects (13)(14)(15) and anticarcinogenic properties (16)(17)(18). The latter effect seems to be related to macrophage activity and recent studies have demonstrated that Lactobacillus and other lactic acid bacteria can increase the phagocytic capacity and enzymatic activity of mouse peritoneal cells (19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%